2016
DOI: 10.1371/journal.pone.0166831
|View full text |Cite
|
Sign up to set email alerts
|

Denervation-Induced Activation of the Standard Proteasome and Immunoproteasome

Abstract: The standard 26S proteasome is responsible for the majority of myofibrillar protein degradation leading to muscle atrophy. The immunoproteasome is an inducible form of the proteasome. While its function has been linked to conditions of atrophy, its contribution to muscle proteolysis remains unclear. Therefore, the purpose of this study was to determine if the immunoproteasome plays a role in skeletal muscle atrophy induced by denervation. Adult male C57BL/6 wild type (WT) and immunoproteasome knockout lmp7-/-/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 46 publications
(67 reference statements)
1
21
0
Order By: Relevance
“…Together, no measureable differences in β1, β5, PA28α, Rpt1 or α7 protein content were present between WT and LMP7/MECL1 deficient muscle in the unstressed state, similar to what we have recently reported in 5-7-month-old mice (Liu et al 2016). However, when stressed by a bout of downhill exercise, WT muscle significantly upregulated LMP7 content while L7M1 muscle instead increased β5 content.…”
Section: Proteasome Contentsupporting
confidence: 87%
See 4 more Smart Citations
“…Together, no measureable differences in β1, β5, PA28α, Rpt1 or α7 protein content were present between WT and LMP7/MECL1 deficient muscle in the unstressed state, similar to what we have recently reported in 5-7-month-old mice (Liu et al 2016). However, when stressed by a bout of downhill exercise, WT muscle significantly upregulated LMP7 content while L7M1 muscle instead increased β5 content.…”
Section: Proteasome Contentsupporting
confidence: 87%
“…Although this is the first report to demonstrate LMP7 content increases in skeletal muscle due to unaccustomed exercise, previous studies have observed LMP7 is upregulated in numerous atrophic models. In fact, data from several laboratories, including our own, have shown elevated LMP7 content in aged (Ferrington et al 2005;Husom et al 2004), denervated (Liu et al 2016), dystrophic (Chen et al 2014;Farini et al 2016) and myopathic (Bhattarai et al 2016) skeletal muscles. Most of these reports also demonstrated LMP2 and/or MECL1 content, the immunoproteasome's other catalytic subunits, increased in parallel to LMP7.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations